2017
DOI: 10.1093/mnras/stx2740
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnetic fields and ambipolar diffusion on the column density probability distribution function in molecular clouds

Abstract: Simulations generally show that non-self-gravitating clouds have a lognormal column density (Σ) probability distribution function (PDF), while self-gravitating clouds with active star formation develop a distinct power-law tail at high column density. Although the growth of the power law can be attributed to gravitational contraction leading to the formation of condensed cores, it is often debated if an observed lognormal shape is a direct consequence of supersonic turbulence alone, or even if it is really obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…We also found that regions with shallower PDF tails show a broad range of global relative orientations of N H and B ⊥ , with the shallowest being those regions where N H and B ⊥ are closer to parallel. These results provide observational evidence of the effects of the magnetic fields in the N H distribution based on MHD simulations (see, e.g., Collins et al 2012;Molina et al 2012;Auddy et al 2018). However, further numerical studies are necessary to determine the physical mechanisms that shape these nearby MCs and properly account for observational effects, such as the mean orientation of the field with respect to the LOS.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We also found that regions with shallower PDF tails show a broad range of global relative orientations of N H and B ⊥ , with the shallowest being those regions where N H and B ⊥ are closer to parallel. These results provide observational evidence of the effects of the magnetic fields in the N H distribution based on MHD simulations (see, e.g., Collins et al 2012;Molina et al 2012;Auddy et al 2018). However, further numerical studies are necessary to determine the physical mechanisms that shape these nearby MCs and properly account for observational effects, such as the mean orientation of the field with respect to the LOS.…”
Section: Discussionsupporting
confidence: 54%
“…More recent studies of MHD turbulence in self-gravitating clouds indicate that the slope of the N H PDF tail is significantly steeper in magnetically subcritical clouds than in supercritical clouds (Auddy et al 2018). These numerical experiments suggest that the magnetic fields act as a density cushion in turbulent gas, shaping the cloud by preventing the gas from reaching very high densities.…”
Section: Relation Of the Relative Orientation To The Distribution Of ...mentioning
confidence: 70%
See 1 more Smart Citation
“…The PDFs show the expected, gravity-driven power-law behaviour at high N (e.g. Kainulainen et al 2009;Kritsuk et al 2011;Girichidis et al 2014;Schneider et al 2015;Auddy et al 2018). However, for a given run there are only marginal differences in the PDFs at N 10 20 cm −2 when considering a different LOS, with the only exception being the run SILCC-MC5.…”
Section: The Column Density Distributionmentioning
confidence: 65%
“…A PLT in the N-PDF is connected to the existence of a powerlaw distribution in volume density and is commonly attributed to the effects of the self-gravity of the gas in generating dense structures in the cloud (e.g., Klessen 2000;Dib & Burkert 2005;Kainulainen et al 2009;Kritsuk et al 2011;Ward et al 2014;Girichidis et al 2014;Schneider et al 2015;Donkov & Stefanov 2018;Corbelli et al 2018;Veltchev et al 2019). Another interpretation for the origin of the first, steep PLT has been proposed by Auddy et al (2018Auddy et al ( , 2019. These authors showed, using numerical simulations of molecular clouds with non-ideal magnetohydrodynamics (MHD), that in the case of a magnetically subcritical cloud, a steep PLT (slope ≈ -4) can emerge as a result of gravitational contraction driven by ambipolar diffusion.…”
Section: Column Density Distribution Functionsmentioning
confidence: 96%